Topical Tenofovir, a Microbicide Effective against HIV, Inhibits Herpes Simplex Virus-2 Replication - Andrei, Graciela; Lisco, Andrea; Vanpouille, Christophe; Introini, Andrea; Balestra, Emanuela; van den Oord, Joost; Cihlar, Tomas; Perno, Carlo-Federico; Snoeck, Robert; Margolis, Leonid; Balzarini, Jan (Cell host & microbe, 2011)
The HIV reverse-transcriptase inhibitor, tenofovir, was recently formulated into a vaginal gel for use as a microbicide. In human trials, a 1% tenofovir gel inhibited HIV sexual transmission by 39% and, surprisingly, herpes simplex virus-2 (HSV-2) transmission by 51%. We demonstrate that the concentration achieved intravaginally with a 1% tenofovir topical gel has direct antiherpetic activity. Tenofovir inhibits the replication of HSV clinical isolates in human embryonic fibroblasts, keratinocytes, and organotypic epithelial 3D rafts, decreases HSV replication in human lymphoid and cervicovaginal tissues ex vivo, and delays HSV-induced lesions and death in topically treated HSV-infected mice. The active tenofovir metabolite inhibits HSV DNA-polymerase and HIV reverse-transcriptase. To exert dual antiviral effects, tenofovir requires topical administration to achieve a drug concentration higher than systemic levels achieved by oral treatment. These findings indicate that a single topical treatment, like tenofovir, can inhibit the transmission of HIV and its copathogens. ► Tenofovir, an anti-HIV drug, inhibits HSV in human cervical tissue ex vivo ► Tenofovir inhibits HSV in human epithelial rafts and delays death of HSV-infected mice ► The active tenofovir metabolite directly inhibits the HSV DNA polymerase ► Topical tenofovir administration is required for its dual anti-HIV/HSV effects